2018
DOI: 10.1177/0963689718807410
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Effects of Conditioned Medium Derived from Mesenchymal Stem Cells on Radiation-Induced Skin Wounds in Rats

Abstract: Radioactive dermatitis is caused by the exposure of skin and mucous membranes to radiation fields. The pathogenesis of radioactive dermatitis is complex and difficult to cure. Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) may serve as a promising candidate for the therapy of cutaneous wounds. The aim of this study was to investigate whether a WJ-MSC-derived conditioned medium (MSC-CM) could be used to treat radiation-induced skin wounds in rats using a radiation-induced cutaneous injury model. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 34 publications
1
60
0
1
Order By: Relevance
“…For instance, an MSC‐CM‐loaded hydrogel promoted angiogenesis and wound healing in a rat model of radiation‐induced skin wounds, with superior performance in vitro and in vivo compared with an EGF‐laden hydrogel positive control. [ 233 ] Another study observed that MSC‐CM embedded in a natural seaweed‐derived material, Carrageenan (CG), or a synthetic poly(vinyl alcohol) (PVA) polymer, enhanced angiogenesis in vitro and in vivo, although MSC‐CM without a biomaterial carrier showed no difference from untreated controls. [ 234 ] MSC‐EVs delivered in a chitosan/silk hydrogel [ 235 ] and in a self‐healing, anti‐bacterial polypeptide hydrogel [ 58 ] promoted cutaneous wound healing in diabetic rat models.…”
Section: Biomaterials Functionalized With Msc Secretomementioning
confidence: 99%
“…For instance, an MSC‐CM‐loaded hydrogel promoted angiogenesis and wound healing in a rat model of radiation‐induced skin wounds, with superior performance in vitro and in vivo compared with an EGF‐laden hydrogel positive control. [ 233 ] Another study observed that MSC‐CM embedded in a natural seaweed‐derived material, Carrageenan (CG), or a synthetic poly(vinyl alcohol) (PVA) polymer, enhanced angiogenesis in vitro and in vivo, although MSC‐CM without a biomaterial carrier showed no difference from untreated controls. [ 234 ] MSC‐EVs delivered in a chitosan/silk hydrogel [ 235 ] and in a self‐healing, anti‐bacterial polypeptide hydrogel [ 58 ] promoted cutaneous wound healing in diabetic rat models.…”
Section: Biomaterials Functionalized With Msc Secretomementioning
confidence: 99%
“…MSC-S derived from Wharton’s jelly (WJ-MSC-S) promotes excisional wound healing in mice through increased cell proliferation [ 58 ]. Recently, WJ-MSC-S has also been shown to promote wound healing in radiation-induced cutaneous wounds of rats [ 59 ].…”
Section: Potential Mechanism Of Action Of Msc-smentioning
confidence: 99%
“…Subcutaneous injection of the WJ‐MSCs suppressed secondary inflammation via reducing inflammatory cytokines and, therefore, promoted burn healing process and skin repair in rat burn models (Zhang et al, 2015). Sun, Zhang, Song, Zhu, and Zhu (2019) assessed the healing effects of these MSCs in radiation‐induced skin injury in rats. They found that WJ‐MSCs improved wound healing quality by promoting cell proliferation, sebaceous glands regeneration, and angiogenesis.…”
Section: Regenerative Effects Of Wj‐mscs In Different Tissuesmentioning
confidence: 99%